Micro Financing implementation and Expansion Strategies of Grameen Bank in Bangladesh (Global Journal of Management and Business Research, 2015)
Grameen Bank (GB) is a micro lending organization in Bangladesh that was initiated by Professor Muhammed Yunus as a pilot project in Jobra village in 1976. It provides small loans to rural poor women, without collateral, following group lending peer support methodologies. It disburses $16.7 billion to 8.67 million borrowers through 2247 branches across Bangladesh. The loan repayment rate is 97%. It is a self-sufficient financial institution. GB's unique program implementation steps make it successful in achieving its goals of creating self-employment and creates choice among rural poor women; thereby increasing their income, empowering them, and promoting environmentalism in rural Bangladesh.
Keywords: Empowerment; human capital; NGOs; self-employment; social capital; and sustainnable development